Website evaluation using the repertory grid technique: a web designers' perspective. - Cheng, Baoxian. (2008)
Kelly's Repertory Grid Technique has been primarily employed to elicit factors that web designers consider important when they design or develop websites, to investigate web designers' perceptions of an "effective" Business-to-Business(B2C) website, and broaden existing web evaluation literature.